CASH MANAGEMENT LEVEL IN MAINTAINING INCOME EFFECTIVENESS THROUGH THE ACCOUNTING MONITORING SYSTEM IN ONE OF THE MSMEs IN BANJARMASIN: CASH MANAGEMENT LEVEL IN MAINTAINING INCOME EFFECTIVENESS THROUGH THE ACCOUNTING MONITORING SYSTEM IN ONE OF THE MSMEs IN BANJARMASIN - Yusri, Yusri; Haikal, Muhammad Erwin (Jurnal Penelitian Ekonomi Dan Akuntansi, 2025)
Banjarmasin, located in South Kalimantan, is home to numerous MSMEs with diverse business activities. To improve these businesses, we identified issues related to accounting among one of the MSMEs studied. These activities generally involve simple recording of income and expenses. Some even fail to record rental space as an expense, making the business appear to generate substantial profits because expenses are not properly recorded. Consequently, the records do not reflect the true financial condition of the business. The problem lies in the lack of direct training on business financial management. To address these issues, training for MSMEs in financial management is necessary for the continuation of this research. Petty cash control can conduct surprise calculations of funds made periodically to determine that the funds are accounted for satisfactorily. Petty cash receipts are canceled or destroyed after being submitted for replenishment, so they cannot be used to request a second replenishment. Based on the results of the study, it is known that the MSMEs are not yet aware that the existing system has weaknesses and a lack of understanding of the system environment in cash control itself, which causes inconsistencies. In this case, it is hoped that information regarding the role of internal cash control can be used as new insights and vice versa to support the smooth administration and accounting so that existing results can function and run as expected. Thus, revenue effectiveness can also be increased.